Analisis Keaktifan dan Hasil Belajar Siswa Melalui Penerapan Model Kooperatif Tipe Learning Together Pada Mata Pelajaran Keamanan Pangan di SMK SMTI Makassar - Karmila; Sukainah, Andi; Novitasari, Ervi (Agricultural Technology Education Study Program, 2023)
This research is a classroom action study that intends to assess the use of the cooperative learning model of the Learning together type and to enhance the active participation and learning results of SMK SMTI Makassar students. In this research, the independent variable is a cooperative model of the sort of dependent variable pertaining to student learning outcomes and activities. 53 class XI PM I and PM III pupils, for a total of 53 individuals, comprised the study's population. 15 persons compose the sample size. Data on learning outcomes are compiled based on student observations and assessments. As data analysis methods, we use activity formulae, study outcomes, and the normalcy gain test. As a consequence of this research, fifty percent of cycle I students, seventy-three percent of cycle II students, and eighty-two percent of cycle III students demonstrated an increase in vitality. This issue became student learning results in the first cycle at 81 percent, the second cycle at 85 percent, and the third cycle at 92 percent, with normality tests acquired in the first cycle at 0.62 percent, the second cycle at 0.70 percent, and the third cycle at 0.85 percent. Therefore, it can be stated that there is an increase in student learning outcomes that are not competent in activities and learning outcomes, with the exception of the cooperative model where the type of Learning together is applied to food security themes rather successfully.